2018
DOI: 10.1002/aoc.4504
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular assembly of hydrogen bonding, ESR studies and theoretical calculations of Cu(II) complexes

Abstract: A series of copper(II) complexes were synthesized by the reaction of copper(II) chlorid with 1‐phenyl‐3methyl‐(3‐dervitives phenylhydrazo)‐5‐pyrazolone (HLn) yields 1:1 and 1:2 (M:L) complexes depending on the reaction conditions. The elemental analysis, spectral (IR, 1H NMR, UV‐Vis and ESR), conductance and magnetic measurements were used to characterize the isolated complexes. The IR spectral data indicate that the metal ions are coordinated through the oxygen of the keto and nitrogen of hydrazone groups. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…According to Hathaway, if G > 4, the exchange interaction is negligible, but G < 4 indicates a considerable exchange interaction. The G value of the complex is 4.10, ruling out the exchange interaction and attributable the tetragonal distortion geometry . This result is in agreement with the magnetic moment value for complex 1 .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…According to Hathaway, if G > 4, the exchange interaction is negligible, but G < 4 indicates a considerable exchange interaction. The G value of the complex is 4.10, ruling out the exchange interaction and attributable the tetragonal distortion geometry . This result is in agreement with the magnetic moment value for complex 1 .…”
Section: Resultssupporting
confidence: 86%
“…The range reported for square planar complexes is 105–135 cm −1 and that for tetragonal distorted complexes is >135–250 cm −1 . Complex 1 has g ll / A ll which lies in the range reported for tetragonal distorted Cu(II) complexes . The ESR study of complex 1 has provided supportive evidence for the conclusion drawn on the basis of the electronic spectrum and magnetic moment value.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The purpose of studying molecular docking is to simulate the molecular recognition process by achieving an optimized conformation for a protein and a drug with relative orientation between them such that the free energy of the overall system is minimized . Exploration of the molecular docking interaction of H 2 L was performed using Docking Server . Affinity of molecules to anticancer receptors is very important in drug design.…”
Section: Resultsmentioning
confidence: 99%
“…The trend of g-tensor values is g ║ >g ┴ >2.0023 suggested that unpaired electron mainly resides in dx 2 -y 2 orbital. Furthermore, the complexes possess g ║ < 2.3, revealing an appreciable metal-ligand covalent character of the complexes [28,29].…”
Section: Spectroscopic Characterizationmentioning
confidence: 99%